Serendipitous formation of photoluminescent carbon quantum dots by mere immersion of a polymer in an organic solvent. (July 2022) - Das, Saroj Kumar; Chakrabarty, Satadru; Gawas, Ramchandra; Jasuja, Kabeer
Highlights: Formation of carbon quantum dots by simply immersing a polymer in an organic solvent is reported Mean size of these quantum dots is around 3 nanometers and thickness around 2–3 nanometers These quantum dots are also nitrogen functionalized High degree of crystallinity also exhibited by these quantum dots Abstract: Carbon quantum dots (CQDs) are 0-dimensional carbon nanoparticles that display quantum confinement effects. Since their first discovery, an impressive library of CQD synthesis schemes has been developed. In this study we present a set of findings, that we came across serendipitously, that lead to an unintended formation of CQDs. We found, that a mere contact between a common polymeric material and an organic solvent resulted in a fluorescent dispersion. Detailed investigations revealed that the dispersion is made up of CQDs. Our analysis shows that these quantum dots exhibit primarily a blue fluorescence and are in the size range of 2–5 nm; these quantum dots are also nitrogen functionalized, and also show a good degree of crystallinity. Such a counterintuitive insight, to the best of our knowledge hasn't been reported earlier. Through this study we aim to bring this strange phenomenon to light and hope that these results would act as helpful inputs in the design of experiments. Graphical abstract: Image, graphical abstract